Influence of Anodization Parameters in the TiO2 Nanotubes Formation on Ti-7.5Mo Alloy Surface for Biomedical Application - Escada, Ana Lucia [UNESP]; Nakazato, Roberto Zenhei [UNESP]; Rosifini Alves Claro, Ana Paula [UNESP] (Univ Fed Sao Carlos, Dept Engenharia Materials, 2017)
In this study, the effects of the parameters such as applied potential difference, time and annealing temperature in the titania nanotubes formation were evaluated. The morphology of the nanotubes was evaluted by using Field Emission Gun - Scanning Electron Microscope (FEG-SEM), Atomic Force Microscope (AFM), contact angle and X-rays diffraction (XRD). Self-organized nano-structures were formed on the Ti-7.5Mo alloy surface from the same electrolyte (glycerol/NH4F) for all conditions. It was observed that the potential influenced the diameter while the length was changed according to the anodization time lenght. The presence of the phases anatase and rutile was altered by annealing temperature. Results showed that 20V-48h-450 degrees C was the better than other conditions for application as biomaterial.
Keywords: Titanium oxide; Nanotubes; Anodic oxidation; Heat treatment